(untitled) (International Journal of Engineering and Computer Science, 2015)
Cloud storage system allows storing of data in to the cloud server efficiently and makes the user to work with the data without any problem, trouble of the resources. Also the Cloud storage permits users to remotely store their data and enjoy it on _demand high quality cloud applications without the burden of local hardware and software management. In existing system data are stored in the cloud using dynamic data operation with computation which makes the user need to make a copy of data for further updating and verification of the data loss unfortunately.